2013
DOI: 10.1093/jxb/ert309
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco LSU-like protein couples sulphur-deficiency response with ethylene signalling pathway

Abstract: Most genes from the plant-specific family encoding Response to Low Sulphur (LSU)-like proteins are strongly induced in sulphur (S)-deficient conditions. The exact role of these proteins remains unclear; however, some data suggest their importance for plants’ adjustment to nutrient deficiency and other environmental stresses. This work established that the regulation of ethylene signalling is a part of plants’ response to S deficiency and showed the interaction between UP9C, a tobacco LSU family member, and one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 42 publications
0
49
0
Order By: Relevance
“…The common participation of similar signals, like ethylene, NO and auxin, in the induction of their responses, could be related to the existence of crosstalk among nutrient deficiencies (reviewed in [3]). According to this view, ethylene, besides P and Fe deficiency responses, is also implicated in the induction of responses to K deficiency [138], to S deficiency [139,140], and to other deficiencies ( [3] and references therein). Recently, Rai et al [141] demonstrated the potential roles of auxin and Zinc (Zn) in mediating local Pi deficiency responses of the root system during growth under different Fe regimes, supporting the existence of crosstalk between Pi, Fe and Zn for maintaining Pi homeostasis.…”
Section: Crosstalk Among Fe and P Deficienciesmentioning
confidence: 99%
“…The common participation of similar signals, like ethylene, NO and auxin, in the induction of their responses, could be related to the existence of crosstalk among nutrient deficiencies (reviewed in [3]). According to this view, ethylene, besides P and Fe deficiency responses, is also implicated in the induction of responses to K deficiency [138], to S deficiency [139,140], and to other deficiencies ( [3] and references therein). Recently, Rai et al [141] demonstrated the potential roles of auxin and Zinc (Zn) in mediating local Pi deficiency responses of the root system during growth under different Fe regimes, supporting the existence of crosstalk between Pi, Fe and Zn for maintaining Pi homeostasis.…”
Section: Crosstalk Among Fe and P Deficienciesmentioning
confidence: 99%
“…In the last 10 years, increased ethylene production by roots and/or shoots has been described for other nutrient deficiencies, such as K (Shin and Schachtman, 2004;Benlloch-González et al, 2010), S (Zuchi et al, 2009;Moniuszko et al, 2013), N (Zheng et al, 2013), and Mg (Hermans et al, 2010). The higher ethylene production described for nutrient deficiencies has been further supported by results showing up-regulation of genes implicated in ethylene synthesis.…”
mentioning
confidence: 83%
“…More recently, a role for ethylene has been extended to other deficiencies, such as K (Shin and Schachtman, 2004;Jung et al, 2009;Kim et al, 2012), S (Maruyama-Nakashita et al, 2006;Wawrzy nska et al, 2010;Moniuszko et al, 2013), and B (Martín-Rejano et al, 2011). Ethylene has also been implicated in both N deficiency and excess Mohd-Radzman et al, 2013;Zheng et al, 2013), and its participation in Mg deficiency has been suggested (Hermans et al, 2010).…”
mentioning
confidence: 99%
“…In tobacco, no specific motifs or domains in LSU/UP9 proteins were detected (Moniuszko et al, 2013). Short and strongly evolutionarily conserved regions were found in various plant LSU proteins, but their functions are unknown (Sirko et al, 2015).…”
Section: Identification and Characterization Of Lsu Genesmentioning
confidence: 99%